A prática pedagógica em desafios junto a um aluno autista - Rezende, Vitor Alves (2024)
This study addresses the professional experiences as a School Support Professional, giving new meaning to inclusive pedagogical practices in challenges together with a non-verbal autistic student with 7 years old at the second year of elementary school. Using a narrative approach and a qualitative research method, the researcher explores the methodological perspectives based on inclusion bibliography, reflecting about his professional experience, as well as the reasons that led him to get involved with the topic. It was used the historical-cultural approach – based on Vygotsky's Historical-Cultural Theory – to develop educational strategies to the autistic child. By collecting reports and declarations from the individuals involved, it sketches an overview in which highlights issues related to the struggle of the rights guarantee in Special Education from an inclusive perspective, given the challenges faced about the effective implementation of laws in the context of teaching in Brazil. The research also brings an in-depth look into the peculiarities of the autistic children development, with emphasis on the redefinition of inclusive educational practices, pedagogical mediations, as well as the link between educate and play. Through teaching practices based on social interactions and many ways of expression, the intimate relationship between affectivity and the teaching process stands out, recognizing the importance of this connection for meaningful learning. As the study unfolds, it reveals the transformations in the views of the professionals involved with this autistic student at school and the redefinition of their mediations and pedagogical practices based on a closer look at the peculiarities of the child's development, which makes the study relevant to the development of more innovative and meaningful educational practices for autistic students.